2018
DOI: 10.1002/mbo3.631
|View full text |Cite
|
Sign up to set email alerts
|

Construction and application of a Xanthomonas campestris CGMCC15155 strain that produces white xanthan gum

Abstract: In the industrial production of xanthan gum using Xanthomonas campestris CGMCC15155, large amounts of ethanol are required to extract xanthan gum from the fermentation broth and remove xanthomonadin impurities. To reduce the amount of ethanol and the overall production cost of xanthan gum, a xanthomonadin-deficient strain of CGMCC15155 was constructed by inserting the Vitreoscilla globin (vgb) gene, under the control of the LacZ promoter, into the region of the pigA gene, which is involved in xanthomonadin syn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(6 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…The pathogen is a gram-negative, rod-shaped bacterium, motile with a single polar flagellum, strictly aerobic, and 0.7 to 1.0 µm by 2.0-2.4 µm in diameter. Other characteristics include producing a yellow, water-insoluble pigment, xanthomonadin and an extracellular polysaccharide (EPS) named xanthan (Dai et al, 2019;Yang et al, 2005). Because of its rapid spread and destructive nature, the European Plant Protection Organization (EPPO) designated the pathogen as an important quarantine organism.…”
Section: Introductionmentioning
confidence: 99%
“…The pathogen is a gram-negative, rod-shaped bacterium, motile with a single polar flagellum, strictly aerobic, and 0.7 to 1.0 µm by 2.0-2.4 µm in diameter. Other characteristics include producing a yellow, water-insoluble pigment, xanthomonadin and an extracellular polysaccharide (EPS) named xanthan (Dai et al, 2019;Yang et al, 2005). Because of its rapid spread and destructive nature, the European Plant Protection Organization (EPPO) designated the pathogen as an important quarantine organism.…”
Section: Introductionmentioning
confidence: 99%
“…Regarding production optimization, it has also been found that xanthan gum molecular properties such the substitution pattern with acetyl and pyruvate groups and thus rheological behaviour can be fine‐tuned on a genetic level (Gansbiller et al ., 2019). Strain genetic engineering also proved feasible to increase whiteness of the xanthan gum product while using lower amounts of ethanol in the downstream processing (Dai et al ., 2019). However, on an industrial scale, this approach may be prohibitive due to regulatory compliance and product labelling.…”
Section: Microbial Polysaccharides: Functionalities and Their Applicability In Industrymentioning
confidence: 99%
“…The FDA approved xanthan gum as a safe polymer in the food industry in 1969; thus, the xanthan products can be found in four grades: crude, industrial, food, and medical auxiliary (28). Despite its high molecular weight (regularly between 2 x 10 6 to 20 x 10 6 Da), the xanthan gum is soluble in cold and hot water, and ethanol, but in this case, intense stirring is needed for dismiss agglomeration.…”
Section: Xanthan Gum Chemistrymentioning
confidence: 99%